Selecting comparables for the valuation of European firms - Ingolf Dittmann; Christian Weiner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper investigates which comparables selection method generates the most precise forecasts when valuing European companies with the enterprise value to EBIT multiple. We also consider the USA as a reference point. It turns out that selecting comparable companies with similar return on assets clearly outperforms selections according to industry membership or total assets. Moreover, we investigate whether comparables should be selected from the same country, from the same region, or from all OECD members. For most European countries, choosing comparables from the 15 European Union member states yields the best forecasts. In contrast, for the UK and the US, comparables should be chosen from the same country only.
Keywords: G19; M41; 330